Problems of Improving the Physical Status of Preschool Children (Eurasian Journal of Learning and Academic Teaching, 2022)
The introduction of modern educational programs and technologies into the educational process, aimed at the comprehensive intellectual, spiritual, aesthetic and physical development of children, a radical increase in the level of preparation of children for school